Secretome analysis of breast cancer cells to identify potential target proteins of Ipomoea turpethum extract-loaded nanoparticles in the tumor microenvironment - Swami, Sanskriti; Mughees, Mohd; Mangangcha, Irengbam Rocky; Kauser, Sana; Wajid, Saima (Frontiers in Cell and Developmental Biology, 2023)
Background: Breast cancer is the leading cause of frequent malignancy and morbidity among women across the globe with an increment of 0.5% incidences every year. The deleterious effects of traditional treatment on off-target surrounding cells, make it difficult to win the battle against breast cancer. Hence, an advancement in the therapeutic approach is crucial. Nanotechnology is one of the emerging methods for precise, targeted, and efficient drug delivery in cells. The previous study has demonstrated the cytotoxic effect of Ipomoea turpethum extract on breast cancer cells delivered via NIPAAM-VP-AA nanoparticles(NVA-IT). Manipulating tumor microenvironment (TME) to inhibit cancer progression, invasion, and metastasis seems to be very insightful for researchers these days. Method: With the help of secretome analysis of breast cancer cells after treatment with NVA-IT, we have tried to find out the possible TME manipulation achieved to favor a better prognosis of the disease. MCF-7 and MDA MB-231 cells were treated with the IC50 value of NVA-IT and the medium was separated from the cells after 24 hours of the treatment. Nano LCMS/MS analysis was performed to identify the secretory proteins in the media. Further bioinformatics tools like GENT2, GSCA, GeneCodis 4, and String were used to identify the key proteins and their interactions. Result: From Nano LCMS/MS analysis, 70 differentially expressed secretory proteins in MCF-7 and 191 in MDA MB-231 were identified in the cell's media. Fifteen key target proteins were filtered using bioinformatic analysis and the interaction of proteins involved in Vesicular trafficking, Cell cycle checkpoints, and Oxidative stress-related proteins was prominent. Conclusion: This study concluded that Ipomoea turpethum extract-loaded NIPAAM-VP-AA nanoparticles alter the secretory proteins constituting the tumor microenvironment to cease cancer cell growth and metastasis.